Hayao Miyazaki Exploring the Early Work of Japan's Greatest Animator - Greenberg, Raz (Animation: Key Films/Filmmakers, 2018)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Hayao Miyazaki's career in animation has made him famous as not only the greatest director of animated features in Japan, the man behind classics as My Neighbour Totoro (1988) and Spirited Away (2001), but also as one of the most influential animators in the world, providing inspiration for animators in Disney, Pixar, Aardman, and many other leading studios. However, the animated features directed by Miyazaki represent only a portion of his 50-year career. Hayao Miyazaki examines his earliest projects in detail, alongside the works of both Japanese and non-Japanese animators and comics artists that Miyazaki encountered throughout his early career, demonstrating how they all contributed to the familiar elements that made Miyazaki's own films respected and admired among both the Japanese and the global audience.